Design And Development Of An Integrated Infield Collection-Transportation Machine For Oil Palm Fresh Fruit Bunch - El Tayeb Ali, Mutasim (2002)
A prototype oil palm FFB Collector-transporter was designed, developed, modified and tested at the Department of Biological and Agricultural Engineering, Universiti Putra Malaysia (UPM), Malaysia. This four-wheeled, hydrostatic drive, integrated machine was designed for collecting and transporting oil palm fresh fruit bunches in the field and unloading them directly into mainline transporters or trucks at the roadside. The overall dimension of the machine was 4750 mm for length, 2040 mm for width and 2725 mm for height. The overall construction of the machine was consisted of a main chassis and driving unit, collection assembly, operator cab, scissors lift-type fruit bin and associated hydraulic control unit. Various functional components of the machine were hydraulically operated through a solenoid control system. ACAD2000 package was employed to develop the 3D model of the prototype machine. A 29.8 kW @ 2200 rpm KUBOTA V2203-E 4- cylinder diesel engine, a 2 1 .5 gpm @ 1000 rpm VICKERS TA1 919 main hydrostatic pump, and a 14.5 gpm @ 1000 rpm SAMHYDRAULIC HIC55 driving motor were selected based on the computations made to determine the machine total engine power and total hydraulic pressure requirements for the machine to operate under local terrain conditions.